Analysis of students’ inhibitions in speaking skill - Disa Afifah; Nani Ronsani Thamrin; Endang Darsih (Universitas Kuningan, 2020)
This paper discusses the phenomenon of students’ inhibitions in speaking skill in Senior High School 2 Kuningan and the solutions. The data which were collected from observation, and interview were analyzed qualitatively. The research participants were 35 students of XI IPS 3 of Senior High School 2 Kuningan. It was found that 5 of 35 students (14.29%) had high score of inhibitions signs (> 60%). As a result, it was found that students’ inhibitions in speaking skill were influenced by internal (low cognitive aspects, and psychological aspects) and external factors (teacher’s role in speaking classroom, classroom atmosphere, and English as foreign language). In order to reduce the inhibitions, the teacher should speak more slowly, create a friendly atmosphere, improve speaking practices, and give appropriate feedback, while the students can explore vocabulary, and ask to a friend whose speaking is better. It is suggested for further researchers to investigate other inhibitions of students speaking skill and the solutions or conduct similar research with different framework.